Differential distribution of beta-tubulin isotypes in cerebellum. - Burgoyne, R D (1988)
We describe the structure and expression of a mammalian beta-tubulin isotype (M beta 6) that is weakly expressed in testis but is abundant in developing brain, with transcripts declining to lower levels in the adult brain. The expression of M beta 6 was undetectable in any other mouse tissue examined. A serum specific for this isotype was prepared using a cloned fusion protein as immunogen. M beta 6 is one of five known beta-tubulin isotypes expressed in brain, and using the anti-M beta 6 serum along with sera, anti-M beta 2, anti-M beta 3/4 and anti-M beta 5, previously characterized, we have examined the pattern of expression of beta-tubulin isotypes in rat cerebellum. The isotypes each have characteristic cell-type specific patterns of localization in cerebellum. M beta 2, M beta 3/4 and M beta 5 are present in both neuronal and non-neuronal cells, but in contrast M beta 6 was only detectable in neurons in tissue sections and in dissociated cerebellar cell culture. The majority of sequence differences among the beta-tubulin isotypes lie at the carboxy terminus, the region of beta-tubulin involved in MAP binding. In the case of M beta 2 and M beta 6, the patterns of expression are similar or identical to the patterns of expression of MAP3 and MAP1A respectively. These results suggest that beta-tubulin isotypes may contribute to the determination of the specific association of MAPs with microtubules of diverse function. However, the strict subcellular segregation of other MAPs in brain may be determined by other factors.